Persepsi Masyarakat Non Muslim Terhadap Prinsip Asas Islam: Perception of Non -Muslim Communities on the Basic Principles of Islam - Meerangani, Khairul Azhar; Mat Johar, Muhammad Hilmi; Abdul Hamid, Mohammad Fahmi (Online Journal of Research in Islamic Studies, 2022)
Building an understanding of the background of cultural and religious diversity in Malaysia is a key thrust in driving harmonious social relations. The nature of mutual understanding that exists in individuals has the potential to create a society that respects and tolerates each other. This foundation of understanding is important in clearing all the confusion and negative perceptions that have enveloped the interaction of the plural society in Malaysia. Thus, this study aims to identify the level of understanding and knowledge of non-Muslims in Melaka on the basic principles of Islam. The study was conducted quantitatively using a survey design. The set of questionnaires was distributed online (google form) to 315 respondents in Melaka, and then analyzed through SPSS software. The findings of the study concluded that the majority of respondents have basic knowledge related to Islam, namely the position of God as god (m = 4.31), the role of the Prophet Muhammad (m = 3.82) and the Quran as a source of reference (m = 3.89). However, some perceptions are still seen in the non -Muslim community, namely Islam is the exclusive religion of the Malays (m = 3.62), Islam is the traditional religion of the Arab community (m = 2.85), is discriminating against women (m = 2.42), not open with other believers (m = 2.38), as well as too many restrictions and prohibitions (m = 3.81). Ultimately, in order to realize the desire to build a concrete foundation of understanding, the commitment of all parties is billed through joint efforts to lead the process of introduction and sharing of basic information on their respective cultural, racial and religious backgrounds. This process is expected to be able to unravel all the propaganda that has often been raised over the years, because human beings are basically only potentially hostile and prejudiced on things that are beyond the limits of their knowledge and understanding.